IMPACT OF HEAVY METALS CONTAMINATION ON THE BIODIVERSITY OF MARINE BENTHIC ORGANISMS IN JAKARTA BAY - Noverita Dian Takarina; Andrio Adiwibowo (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Alteration of land is continuing to increase inorganic matter to marine ecosystems and reduce marine biodiversity. Therefore, we investigated the interplay among land use and heavy metal (Cr, Cu, Pb, Zn) inputs from 8 rivers of Jakarta Bay to the benthic biodiversity. At current time, land uses surrounding Jakarta Bay are fulfilled with industrial activity, settlement, and agriculture. Total concentration of Cr, Cu, Pb, and Zn were determined using the Atomic Absorption Spectrometry in order to assess and compare contamination levels among land use types. Results showed that the average concentrations of heavy metals in sediment were generally higher in river-mouth received water from industrial than those in agriculture. Those land use related metal pattern were also reflected in the benthos diversity. Macrobenthic community diversity decreased when inputs of organic matter increased. Decreases in macrobenthic diversity were mainly linked to an increasing abundance of species with specific functional traits, specifically deposit–feeding polychaetes. Our finding confirmed that land use in the form of industrial areas were potential to produce toxic material to ecosystems. Therefore, we recommend that the development need to consider the allocation of physical infrastructure particularly near waterways.